Self-cultivation philosophies in ancient India, Greece, and China - Gowans, Christopher W. (Oxford University Press, 2021)
"The book defends the thesis that the concept of self-cultivation philosophy is an informative interpretive framework for comprehending and reflecting on several philosophical outlooks in India, the Greco-Roman world and China. On the basis of an understanding of human nature and the place of human beings in the world, self-cultivation philosophies maintain that our lives can and should be substantially transformed from what is judged to be a problematic, untutored condition of human beings, our existential starting-point, into what is put forward as an ideal state of being. We are to do this by undertaking a set of therapeutic or spiritual exercises guided by some philosophical analysis. The self-cultivation philosophies in India are expressed in: the Bhagavad Gītā; the Sāṃkhya and Yoga philosophies of Īśvarakṛṣṇa and Patañjali; and teaching of the Buddha and his followers Buddhaghosa and Śāntideva. The philosophies originating in Greece, with subsequent development in the Roman period, are the most prominent Hellenistic approaches: the Epicureanism of Epicurus, Lucretius and Philodemus; the Stoicism of Chrysippus, Epictetus and Seneca; and Pyrrho and the Pyrrhonism of Sextus Empiricus. The self-cultivation philosophies from China are the early Confucian outlooks of Confucius, Mencius and Xunzi; the classical Daoist perspectives of the Daodejing and the Zhuangzi; and the Chan tradition of Bodhidharma, Huineng and Linji"--